Machine learning techniques in the energy consumption of buildings - Abdelaziz, Ahmed (2021)
109 “Consumo SMART” https://www.simplex.gov.pt/medidas. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.